2006
DOI: 10.1016/j.jacc.2005.12.055
|View full text |Cite
|
Sign up to set email alerts
|

Serofendic Acid, a Novel Substance Extracted From Fetal Calf Serum, Protects Against Oxidative Stress in Neonatal Rat Cardiac Myocytes

Abstract: Serofendic acid protects cardiac myocytes against oxidant-induced cell death by preserving the functional integrity of mitochondria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 32 publications
2
25
0
Order By: Relevance
“…It is a lowmolecularweight (MW 382) compound and exhibits a potent protective effect against neurotoxicity induced by glutamate, NO, and oxidative stress without inhibiting glutamate receptors in cultured cortical, striatal, and spinal cord neurons (23 -26). Moreover, in cardiac myocytes, serofendic acid was found to suppress cell death induced by oxidative stress (27,28). The mechanism of protection remains unclear, but we have demonstrated that serofendic acid preserves mitochondrial functional integrity and inhibits the generation of hydroxyl radical and caspase3 activation (23,24,26,27).…”
Section: Serofendic Acid Protects Against Myocardial Ischemia-reperfumentioning
confidence: 83%
See 4 more Smart Citations
“…It is a lowmolecularweight (MW 382) compound and exhibits a potent protective effect against neurotoxicity induced by glutamate, NO, and oxidative stress without inhibiting glutamate receptors in cultured cortical, striatal, and spinal cord neurons (23 -26). Moreover, in cardiac myocytes, serofendic acid was found to suppress cell death induced by oxidative stress (27,28). The mechanism of protection remains unclear, but we have demonstrated that serofendic acid preserves mitochondrial functional integrity and inhibits the generation of hydroxyl radical and caspase3 activation (23,24,26,27).…”
Section: Serofendic Acid Protects Against Myocardial Ischemia-reperfumentioning
confidence: 83%
“…It may partially contribute to myocardial protection because ROS is an important inducer of collapsing mitochondrial integrity followed by cell death. In fact, serofendic acid prevented ROS accumulation induced by H2O2 in neonatal rat cardiac myocytes (27). Moreover, serofendic acid inhibited caspase3 activation and reduced TUNELpositive cells in cardiac myocytes and cortical neurons (26,27).…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations